Expression of neutrophil extracellular trap-related proteins and its correlation with IL-17 and TNF-α in patients with oral lichen planus - Cheng, Juehua; Zhou, Chenyu; Liu, Jia; Geng, Yanlin; Liu, Lin; Fan, Yuan (PeerJ, 2024)
Background Neutrophil extracellular traps (NETs) are produced by polymorphonuclear neutrophils (PMNs) stimulated by interleukin-17 (IL-17) and tumor necrosis factor α (TNF-α). However, the level and role of NETs in oral lichen planus (OLP) remain poorly understood. Objective This study aimed to investigate the expression of NETs in OLP and explore the correlation between NETs and the levels of IL-17 and TNF-α. Methods The expression and distribution of NET-related proteins in tissue samples from each group were assessed using hematoxylin-eosin (HE) staining and immunofluorescence (IF). Additionally, the expression of NET-related proteins in peripheral blood samples from each group was evaluated using cell IF technique and fluorescence spectrophotometry. The relative formation level of NETs in each group was determined by fluorescence spectrophotometry via plasma co-culture. Furthermore, the levels of inflammatory cytokines IL-17 and TNF-α in plasma and culture supernatant were measured using enzyme-linked immunosorbent assay (ELISA). Results NET-related proteins were located in the subepithelial and lamina propria layers of OLP lesions. OLP had significantly higher expression of NET-related proteins in lesion tissues and peripheral blood compared to the healthy control (HC) group (p < 0.05). The rate of NETs formation in the erosive-stage OLP (EOLP) group was significantly higher than that in the HC group (p < 0.05), in contrast, no significant increase was observed in the non-erosive OLP (NEOLP) group (p > 0.05). Furthermore, the levels of IL-17 and TNF-α in the EOLP group were significantly elevated compared to those in the NEOLP group and HC group (p < 0.05), while the levels in the NEOLP group did not significantly differ from those in the HC group (p > 0.05). The rate of NETs formation showed a positive correlation with the levels of IL-17 and TNF-α in plasma. Conclusion The expression of NET-related proteins was upregulated in OLP lesion tissues and peripheral blood. Elevated levels of IL-17 and TNF-α in peripheral blood plasma positively correlated with the rate of NETs formation, suggesting that IL-17 and TNF-α mediate the formation of NETs in OLP patients, and may thereby contribute to the development of OLP.
Keywords: Oral lichen planus; Neutrophil extracellular traps; Interleukin-17; Tumor necrosis factor α